(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The effectiveness of educational activities is the main criterion as the best criterion for assessing the level of quality of the educational process. In each education system (primary, general, secondary specialized, higher), the main task and goal is to increase the effectiveness of educational activities. Factors influencing the effectiveness of educational activities and the dynamics of educational effectiveness are one of the pressing issues in psychology.